PEMBUATAN NATA DE RICE DARI AIR CUCIAN BERAS DALAM BEBERAPA KONSENTRASI DENGAN BAKTERI Acetobacter xylinum - A. Suparlan Isya Syamsu; Sirajul Firdaus; Ali Imran (Fakultas Farmasi UMI, 2015)
The research has maked nata De rice water in several concentrations using bacteria Acetobacter xylinum. This study aims to determine the concentration of the right rice washing water, which meets the criteria of thickness, texture and color nata most optimum. This study uses three rice water concentration of 25%, 50% and 75%, with the addition of 10% sugar. Nata formation is based on the decomposition of sugar into a pellicle layer cellulose (nata). The cellulose layer thickness calculated using the rule and the specified quality textures and colors to use assessment of panelists. The final conclusion is that making nata of rice washing water indicates nata layer. This study showed that the addition of rice washing water at a concentration of 75% produces nata with a thickness of 2 cm with a good texture and color.